Ecoando vozes subalternizadas : uma experiência de/colonial e antirracista de educação linguística em sala de aula de ensino médio - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The text proposal is to promote the voices of people subalternize by the Eurocentric model of thinking about knowledge, from conversations about racism with high school students from a public school in Goiás, focused in problematizations about the racist and subtle culture that we consume daily through some institutional spaces, showing the subtlety that racism is internalized in us through the media. This pedagogical attitude left from my experience as a student, a period in which I often wanted to speak, expose what I thought and/or felt, and I was never given the space in speech (SILVESTRE, 2016). Thus, I decided to use my conquered space of privilege to try to make some silenced voices echo. Feeling a lack of subaltern knowledge at school and in scientific research, especially on racism, I proposed to look for other ways to produce such knowledge. In this way, I based myself on Mignolo's (2003) perspective not to research about, but to research with. Therefore, what some Eurocentric researches call data, in this dissertation, will be seen as knowledge, that is, thoughts materialized through language. Understanding linguistic learning as something transdisciplinary, and even antidisciplinary (PENNYCOOK, 2006), I base myself on some knowledge from different areas, but complementary to language, such as decolonial studies (CASTRO-GÓMES, 2005; COSTA; TORRES; GROSFOGUEL, 2018; GROSFOGUEL, 2018; GROSFOGUEL , 2008, 2006; QUIJANO, 1992, 2005), transdisciplinary (BRANCO, 2005; FANON, 1968, 2008; FAZZI, 2008; GRAMSCI, 1999; HOLANDA, 1995; MATTOZO, 2003; MOURA, 1977; MURANGA, 1999, 2000; SPIVAK, 2010; KILOMBA, 2019), cognitive (CORTEZ, 2005; FERRARI, 2011; LAKOFF; JOHNSON, 2002; SILVA, 2012) and language critics (FABRÍCIO, 2006; FAIRCLOUGH, 2001, 2010; MOITA LOPES, 1996, 2006 , 2009, 2019; NASCIMENTO, 2019; OLIVEIRA, 2013; PENNYCOOK, 2006; RAJAGOPALAN, 2007), among others, which corroborate the reflections presented here. This research/teaching is decolonial with a desire to be anti-racist, carried out in May and June 2021, through seven remote meetings, conducted on Tuesdays with apprentices from the third year of high school in a public institution. To carry out these meetings, the Google Meet platform was used, due to the atypical moment we are experiencing, space in which the conversations was promoted. To record the knowledges presented, all meetings were recorded in audio and video. The results indicate the need and possibility of highlighting the voices of subalternizes in our privileged spaces. In addition, this research/teaching also allowed us to realize that the culture we consume, through the media, is so "naturalized" in our daily lives that we do not easily perceive the racism that is transmitted and fused to what we know as "popular culture".
Echoing subaltern voices : a de/colonial and anti-racist experience of language education in high school classrooms
Keywords: Decolonialidade; Conhecimento subalterno; Língua e cultura racista; Racismo; Decoloniality; Subaltern knowledge; Racism; Racist language and culture; LINGUISTICA, LETRAS E ARTES::LINGUISTICA